Projekt Atractiv: zlepseni kardiovaskulárni prevence v podmínkách primárni péce v Ceské republice - Vrablík, M; Freiberger, T; Lánská, V; Ceska, R (Vnitrni lekarstvi, 2008)
INTRODUCTION: The Atractiv project assessing the efficacy ofa complex approach to cardiovascular risk reduction in primary care was conducted by 464 physicians in the entire Czech Republic between 2006 and 2007. AIM: The primary goals of the Atractiv project were description of prevalence of risk factors for cardiovascular disease (CVD) in high-risk patients and attempt to maximize the risk reduction by optimalization of treatment. Within five visits the patients were carefully followed and their risk factors were intervened using lifestyle and pharmacological measures. METHODS: The main focus of the project was management of dyslipidemia and arterial hypertension. Basic anthropometric and laboratory data were collected including serum lipids, glycemia, kidney liver function tests, CVD risk was assessed using SCORE charts. 4,427 patients were included in the project (2,372 men), average age 62.9 +/- 10 years. RESULTS: Optimalization of treatment of dyslipidemia resulted in a significant decrease of both total and LDL-cholesterol levels by 23 and 28%, respectively, HDL-cholesterol concentrations increased by 4.5% and levels of triglycerides declined by 22%. Improved management of arterial hypertension was accompanied by a decrease of average blood pressure from 152.5/90.5mm Hg to 132.5/80.2mm Hg. Average fasting glycemia was lowered by 0.4 mmol/l while body mass index and waist circumference decreased by 0.6 kg/m2 and 2.5 cm, respectively. All differences between baseline and the last visit were statistically significant (p < 0.001). Pharmacotherapy indicated during the project was well tolerated and occurrence of side effects was minimal. CONCLUSION: The Atractiv project documents the complex approach to patients at high-risk of CVD including lifestyle intervention with effective combination of lipid-lowering drugs and antihypertensive drugs brings additional significant lowering of CVD risk. Application of modern, evidence-based approaches to treatment of dyslipidemia and arterial hypertension in everyday practice is possible, effective and feasible.
Keywords: Female; Dyslipidemias; ženské pohlaví; lidé; Risk Factors; Male; Cardiovascular Diseases; Czech Republic; dyslipidemie; primární zdravotní péče; rizikové faktory; kardiovaskulární nemoci; Primary Health Care; Česká republika; lidé středního věku; mužské pohlaví; Middle Aged; komplexní zdravotní péče; Comprehensive Health Care; Humans